The Geography of Religious and Confessional Structures in the Crown of the Polish Kingdom in the Second Half of the Eighteenth Century - Szady, Bogumił (Polish Studies - Transdisciplinary Perspectives, 2019)
The book minutely depicts the territorial organization of religions and confessions in the Crown part of the Polish-Lithuanian Commonwealth in the second half of the eighteenth century. It focuses on the spatial range and variety of the communities in the region, which was a melting pot of many different religions, confessions and denominations. The picture the book paints owes its depth and detail both to the characterization of the borderlands, and to the heterogeneous and homogeneous zones. Prof. Michael Müller: "The book represents a methodologically most innovative, and empirically very rich, contribution to at least three fields of study: historical geography, religious history and historical demography. For the first time, we get a full, and reliable, picture of the churches of all Christian denominations and of the synagogues (and of the religious institutions and organizations behind them) that existed in the lands of the Crown prior to the first partition of Poland."